A word of caution regarding Ceftriaxone - Naveen Azhar; Arooma shaukat, Arooma Shaukat; Navaira Shoaib, Navaira Shoaib (Journal of the Pakistan Medical Association, 2021)
Ceftriaxone is a well-known antibiotic belonging to the third generation of cephalosporins. This broad-spectrum drug is highly effective against gram negative and gram-positive bacterial infections and is frequently used to treat severe bacterial infections in pediatrics, including disseminated gonococcal infections, sepsis and meningitis. However, concerns have been raised regarding the drug’s safety as it is prone to various side effects like bilirubin encephalopathy, cholestasis, pseudolithiasis and rarely hepatitis and pancreatitis.1 A prospective study in 154 children published in Human and Experimental Toxicology in 2016 further validate this point.2 According to this study, out of 84, 20.9% children treated with ceftriaxone had abnormal biliary sonographic findings and 15.1% had biliary lithiasis whereas cefotaxime was found to be comparatively safer. Worrying facts related to Ceftriaxone should definitely be taken into consideration as ceftriaxone is a standard treatment for several bacterial infections in children and is being prescribed at a regular basis in many countries. In fact, a clinical study performed in a secondary care hospital of Karachi, Pakistan, declared it the most frequently prescribed antibiotic.3 Physicians should prescribe ceftriaxone with caution. Ceftriaxone should be avoided in neonates especially those with hyperbilirubinemia. Caution must be advised for the use of intravenous ceftriaxone with intravenous calcium containing solutions as their concomitant use can lead to life threatening adverse reactions.4 Patient should seek medical help if they experience diarrhea, jaundice, confusion, headache, heart palpitations etc. Similar drugs with a safer adverse effect profile should be considered as a future alternative. Continuous..